Microbes in biotechnological applications - Huyop, Fahrul Zaman (Penerbit UTM Press, Universiti Teknologi Malaysia, 2017)
This book explains the various microbes that may potentially be used for different applications in biotechnology. This book first presents the moderately halothermophilic organism strain RA previously isolated from a hot spring on Langkawi Island. This new strain was characterized and identified as a novel species belonging to the family of Rhodothermaceae. The next chapter presents the isolation of bacteriophages from soil which are specific to B. subtilis. The preliminary observation suggests it has the potential to be used as a component in biofertilizer. Chapter 3 highlights a study on probiotics is currently gaining popularity among researchers. The study isolated a Lactobacillus sp. from a Malaysian fermented food using specific primers Lacto-16S-F/R. Probiotic microorganisms i.e. Lactobacillus sp. can aid in the improvement of microbial flora in the human intestine. The following chapter explores the isolation of a lipase-producing microorganism, Arthrobacter sp. from the Antarctic continent. The final chapter investigates the isolation of Aspergillus sp., an Ascomycetes fungi and Mycelia sterilia in samples of traditional medicine sold in stores and markets. The order of microbial prevalence in such samples possibly due to improper storage are as follows: Genus Aspergillus followed by Ascomycetes fungi and Mycelia sterilia. Therefore, consumption of such contaminated traditional medicine may impart potential health risks to the consumers, especially those with compromised immune systems.